2004
DOI: 10.1044/1092-4388(2004/109)
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Written Language Deficits in Children With SLI

Abstract: Children with specific language impairment (SLI) have associated difficulties in reading decoding and reading comprehension. To date, few research studies have examined the children's written language. The aim of the present study was to (a) evaluate the nature and extent of the children's difficulties with writing and (b) investigate the relationship between oral and written language. Eleven children with SLI were identified (mean age = 11 years) and were compared with a group of children matched for chronolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
144
2
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(186 citation statements)
references
References 46 publications
(39 reference statements)
20
144
2
20
Order By: Relevance
“…For instance, several studies have failed to find any reliable relationship between children's grammatical skills (or oral language skills) and the structural quality of their written compositions (Berninger, et al, 1992;Griffin, Hemphill, Camp, & Wolf, 2004;Mackie & Dockrell, 2004). Likewise, some studies have failed to find any reliable relationships between children's writing fluency and writing quality (Fey, et al, 2004).…”
Section: Composition Writingmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, several studies have failed to find any reliable relationship between children's grammatical skills (or oral language skills) and the structural quality of their written compositions (Berninger, et al, 1992;Griffin, Hemphill, Camp, & Wolf, 2004;Mackie & Dockrell, 2004). Likewise, some studies have failed to find any reliable relationships between children's writing fluency and writing quality (Fey, et al, 2004).…”
Section: Composition Writingmentioning
confidence: 96%
“…This may partly suggest that other processes were influencing children's spelling performance whilst composing text. Children can clearly be more selective and choose words that they know and can spell well (see Mackie & Dockrell, 2004). They may also make spelling mistakes because of limitations in information processing or attentional resources.…”
Section: Longitudinal Predictors Of Reading and Spellingmentioning
confidence: 99%
“…In the sentence-combining task, students were given a pre-determined set of sentences and had a narrow range of options to correctly combine them (Berninger et al, 2011;Strong, 1986). Spelling accuracy was assessed in the context of writing, in the opinion essays with and without planning Limpo & Alves, 2013a;Mackie & Dockrell, 2004;Nelson & van Meter, 2007;Wagner et al, 2011). The opinion essay without planning was only used to extract writing performance measures, excepting one of the spelling measures.…”
Section: Discussionmentioning
confidence: 99%
“…This spelling measure has been used extensively in prior research with good evidence for validity Limpo & Alves, 2013a;Mackie & Dockrell, 2004;Nelson & van Meter, 2007;Wagner et al, 2011). Additionally, other studies have found that spelling in text is moderately correlated with spelling-to-dictation measures (Graham et al, 1997;Limpo & Alves, 2013a).…”
Section: Spelling Accuracy Measuresmentioning
confidence: 99%
“…De même, Mackie et Dockrell (2004) ont montré que les participants dysphasiques de 11 ans produisent plus d'omissions de flexions verbales sur les personnes (le « s » de la troisième personne du singulier) et sur les temps (« ing » et « ed ») que les participants typiques du même âge. Par ailleurs, les recherches déjà menées à l'écrit n'abordent jamais la question des différentes catégories d'erreurs d'orthographe lexicale (Bishop, & Clarkson, 2003 ;Dockrell, Lindsay, & Connelly, 2007 ;2009 ;Fey, Catts, Proctor-Williams, Tomblin, & Zhang, 2004 ;Mackie, & Dockrell, 2004 ;Windsor, Scott, & Street, 2000).…”
Section: Introductionunclassified